Association between Serum Alpha-Synuclein Levels and Parkinson's Disease Stage - Yuliarni Syafrita; Restu Susanti (Universitas Islam Bandung, 2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's. It is chronically progressive with the main symptoms of resting tremor, rigidity, bradykinesia, and postural disturbances. Lewy's body and Lewy's neurite are the main findings in brain biopsies of patients with PD. The main component is alpha-synuclein, a misfolding protein that plays an essential role in the pathogenesis of PD. This study aims to determine the association between serum alpha-synuclein levels during the PD stage and compare the levels between PD patients and healthy populations of the same age. A case-control study was conducted on 62 people with PD and 20 normal subjects as controls in the outpatient Department of Neurology of Dr. M. Djamil General Hospital and Ibnu Sina Islamic Hospital, Padang, from March to September 2020. The ELISA method examined serum alpha-synuclein examination, and the PD stage was assessed according to Hoehn and Yahr stages. The differences in alpha-synuclein levels between cases and controls and between stages of PD were analyzed by the Mann-Whitney test. Alpha-synuclein levels in PD patients were higher than in controls, and this difference was statistically significant (p<0.05). On the other hand, alpha-synuclein levels were higher in the severe stage than in the mild stage but not statistically significant (p>0.05). In conclusion, there was no association between alpha-synuclein levels and the stage of Parkinson's disease. Still, serum alpha-synuclein levels in PD patients were significantly higher than in the healthy population.